2016
DOI: 10.1080/15428052.2016.1225538
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of a Head Chef: Exploring Factors Influencing Success in Irish Kitchens

Abstract: One-hundred and seventy head chefs from the Republic of Ireland scored 59 variables for success on two scales: (a) competencies needed for success (NS), and (b) personal ownership of these competencies (PO). Results showed that variables were rated with means of 1.18 (extremely important) to 3.23 (moderately important). The top three were an ability to work hard, commitment to quality, and knowledge of Hazard Analysis and Critical Control Points (HACCP). Variables rated lower in ownership than importance highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 86 publications
(173 reference statements)
0
25
0
Order By: Relevance
“…This research opined that horizontal leadership practices in the restaurant industry leads to the possibility of a new order for growth and development. In addition, the factors needed to succeed in the culinary industry include professionalism, individual characteristics, leadership skills, management skills, and interactions with work contexts (Allen & Mac Con Iomaire, 2017). Furthermore, according to this study, efforts to strengthen the hotel industry in the future include talent management, guiding future leaders, reducing staff turnover, and curriculum development.…”
Section: Interpersonalmentioning
confidence: 86%
See 4 more Smart Citations
“…This research opined that horizontal leadership practices in the restaurant industry leads to the possibility of a new order for growth and development. In addition, the factors needed to succeed in the culinary industry include professionalism, individual characteristics, leadership skills, management skills, and interactions with work contexts (Allen & Mac Con Iomaire, 2017). Furthermore, according to this study, efforts to strengthen the hotel industry in the future include talent management, guiding future leaders, reducing staff turnover, and curriculum development.…”
Section: Interpersonalmentioning
confidence: 86%
“…This fact is significant in a restaurant, where unhealthy conditions can affect the quality of food, and can even force a restaurant to close. The study conducted by Allen and Mac Con Iomaire (2017) revealed that there are three top criteria for chef success in Ireland, namely hard work, commitment to quality, and Hazard Analysis and Critical Control Points (HACCP).…”
Section: Conceptual (Innovation Creativity and Aesthetics)mentioning
confidence: 99%
See 3 more Smart Citations